2017
DOI: 10.1097/scs.0000000000003234
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Epidemiology of Orofacial Clefts in Ethiopia

Abstract: Background-The prevalence of birth defects including orofacial clefts (OFC) in Ethiopia is not known and there is no established birth defects registration system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
3
8
0
Order By: Relevance
“…This prevalence rate could be underestimated, because it excludes stillbirths, abortions and those children who might have died within the first three months of birth, or before seeking care. Nonetheless, this rate is also comparable to those found in Nigeria of 0.5 per 1000 live births [39] and higher than that of Ethiopia at 0.2 per 1000 live births [38]. In contrast, the prevalence rate reported in our study is lower than the rates reported for a population base birth defects registries from 30 countries from 54 international craniofacial registries during the period 2000 to 2005, where the overall prevalence of CLP was 1.0 per 1000 [51].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This prevalence rate could be underestimated, because it excludes stillbirths, abortions and those children who might have died within the first three months of birth, or before seeking care. Nonetheless, this rate is also comparable to those found in Nigeria of 0.5 per 1000 live births [39] and higher than that of Ethiopia at 0.2 per 1000 live births [38]. In contrast, the prevalence rate reported in our study is lower than the rates reported for a population base birth defects registries from 30 countries from 54 international craniofacial registries during the period 2000 to 2005, where the overall prevalence of CLP was 1.0 per 1000 [51].…”
Section: Discussionsupporting
confidence: 82%
“…In many African countries, active population based surveillance systems are not available. Prevalence is estimated from hospital-based data, and ranges from 0.2/1000 live births in Ethiopia [38], 0.5/1000 in Nigeria [39], 0.8/1000 in Uganda [22] and 1.7/1000 reported in Kenya [40]. A community household survey in South East Ghana found an estimated prevalence of 6.3/1000 people with CLP [41], however CLP was measured through community self-reporting rather than clinical examination.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 9 ] Other studies also show similar gender distribution patterns. [ 10 11 12 13 14 15 ] CLA was the most common diagnosis made which concur with previous local studies which also showed a similar trend. [ 15 16 ] Other authors have however reported CL and palate to be more prevalent in their centers.…”
Section: Discussionsupporting
confidence: 88%
“…This delayed age of consultation has also been reported in other LMICs. [49][50][51] Lip surgery provides comfort to the parents of CLP children, as they are able to show their children in public and avoid stigmatisation. Strategies need to be developed to ensure that the majority of children with CLP have access to lip surgery within the first 6 months of life.…”
Section: Researchmentioning
confidence: 99%